1970
DOI: 10.2134/agronj1970.00021962006200020012x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen and Potassium Fertilizers and Dates of Seeding on Yield and Quality of Malting Barley1

Abstract: Thirteen field trials were conducted to test the effects of rates of N and K fertilizers and seeding dates differing by 2 weeks upon yield, percentage plump kernels, and protein content of malting barley. N fertilizer increased average grain yields on early‐seeded plots by 253, 410, and 534 kg/ha for 22.4, 44.8, and 67.2 kg N/ha, respectively. On late‐seeded plots, same rates of N increased average yields by 264, 303, and 389 kg/ha, respectively. Late seeding reduced average grain yields by 295 kg/ha. Rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
1

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 10 publications
5
36
1
Order By: Relevance
“…Thus seed-placement of KCl on soils with high K levels had no impact on quality characteristics of barley. This agrees with the findings by Mohr et al (1995b), but contrasts those by Zubriski et al (1970) who observed that K application at 14 and 28 kg K ha -1 resulted in increased plumpness of barley by 1.3 and 1.7% on early-seeded plots and 1.8 and 2.7% on late-seeded plots, respectively. CONCLUSION Certain barley varieties grown on western Canadian prairie soils containing high "available" potassium levels do respond to seed-row-applied KCl.…”
Section: Effect Of Kcl On Days To Maturity and Barley Grain Protein Asupporting
confidence: 89%
“…Thus seed-placement of KCl on soils with high K levels had no impact on quality characteristics of barley. This agrees with the findings by Mohr et al (1995b), but contrasts those by Zubriski et al (1970) who observed that K application at 14 and 28 kg K ha -1 resulted in increased plumpness of barley by 1.3 and 1.7% on early-seeded plots and 1.8 and 2.7% on late-seeded plots, respectively. CONCLUSION Certain barley varieties grown on western Canadian prairie soils containing high "available" potassium levels do respond to seed-row-applied KCl.…”
Section: Effect Of Kcl On Days To Maturity and Barley Grain Protein Asupporting
confidence: 89%
“…, barley (Zubriski et al 1970;Last 1957;Jessop and Ivins 1970) and wheat (Jessop and (Last 1957;Cannell 1969;Spiertz et al 1971); reduced total dry matter, grain-straw ratio, leaf area index and grain number per ear of barley and wheat (Jessop and Ivins 1970); increased incidence of powdery mildew (Erysiphe graminis DC. ) in barley and wheat (Last 1957); increased frit fly (Oscinella frit L.) attack in oats (Tesic 1968); and reduced green area duration of spring wheat (Spiertz et al 197 l).…”
mentioning
confidence: 99%
“…) in barley and wheat (Last 1957); increased frit fly (Oscinella frit L.) attack in oats (Tesic 1968); and reduced green area duration of spring wheat (Spiertz et al 197 l). However, grain protein content of barley increased (Kirby 1969) or decreased (Hoag and Geiszler 1968;Zubriski et al 1970) with late seeding. Schmidt (1960) In 19'73, the seed treatment significantly increased the yield of the first two seedings of barley, but showed no effect on oats (Table 3).…”
mentioning
confidence: 99%
“…1B). Previous studies have shown barley kernel plumpness usually decreased with increasing N rate but the results were sometimes inconsistent among locations and years (Zubriski et al 1970;Lauer and Partridge 1990;McKenzie et al 2005;O'Donovan et al 2011). Preceding crop had no effect on either germination energy or germination index while N rate had no effect on germination energy (Tables 1 and 2).…”
Section: Grain Quality Parametersmentioning
confidence: 94%